Strategi Marketing Public Relations Hotel Neo Malioboro dalam Meningkatkan Pengunjung di Masa Pandemi Covid-19 - Wahyu Rasyidi; Mufid Salim (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2022)
Yogyakarta's Hotel NEO Malioboro is one of the city's three-star lodgings. This hotel, which is under the management of Archipelago International, promises a modern brand with modern and beautiful interior spaces. NEO Malioboro is a mainstay for out-of-town tourists to stay because of its very strategic location from the city center. Coronavirus makes Hotel NEO Malioboro lose visitors. Government policies that led to restrictions on community activities made tourism closed again breaking the chain of the spread of the Corona Virus. This study aims to analyze how the role and handling of a public relations officer in dealing with the pandemic situation and visitor crisis that befell Hotel NEO Malioboro. Hotel NEO's public relations measures will be analyzed to deal with the visitor crisis and increase the positive brand in the public sphere. So with that, the role of public relations is very necessary to overcome this potential so that Hotel NEO does not die in the storm of the Covid-19 pandemic. This research method uses a qualitative descriptive research approach, with Hotel NEO Malioboro as the object of research. This study uses data collection techniques based on in-depth interviews, observations, and documentation. The resource persons are public relations, the Director of sales, and a Graphic designer, while the other three speakers are respondents/visitors. Data analysis is divided into three stages: data reduction, data display, verification, and conclusion. The triangulation method is a measure of the validity and correctness of the data through data validation. The results of this study indicate that the marketing strategy carried out by public relations uses a pull strategy, pass strategy, and push strategy by maintaining customer loyalty and then is broken down with a public relations strategy process through the stages of defining problems, planning, and programming, taking action and communication, and ends with an evaluation. The number of visitors to Hotel NEO Malioboro has increased drastically after PPKM. According to insight data, viewers on various social media have also increased. The use of marketing public relations strategies can be said to be able to attract visitors back to Hotel NEO Malioboro which is experiencing a visitor crisis.